Urban gardening as a risk-reduction strategy - an intersectional analysis of top-down gardening initiatives - Larsson, Emelie; Giritli Nygren, Katarina (Journal of risk research, 2024)
In cities around the world, urban gardening is increasingly used as a municipal strategy to tackle both environmental and social risks. In this study we draw on critical and intersectional studies of risk to analyse municipalities' framing of urban gardening as a way to illuminate how it is entangled with contemporary structures of power. The material consists of strategy documents and information on the municipalities' websites, and the texts were analysed using critical discourse analysis, which enabled us to integrate a sociocultural, an intersectional and an ecopolitical theoretical approach to risk. We identified two discourses: an eco(no)logical risk discourse where ecological risks were addressed within a capitalist market logic, and a social risk discourse, where focus was on gardening as work training and integration. We found that within these discourses, several gardening subjects appeared, and these could be positioned as either capable of solving and/or mitigating risks, or as at risk and in need of intervention. The results show how the top-down initiating of urban gardens display contemporary inequalities in urban spaces, which are crucial to identify in order to create city spaces that are safe, inclusive and enjoyable for all citizens.